2015
DOI: 10.5688/ajpe79115
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Educational Technology to Improve Patient Care in Pharmacy Curricula

Abstract: A review of the literature on the effectiveness of educational technologies to teach patient care skills to pharmacy students was conducted. Nineteen articles met inclusion criteria for the review. Seven of the articles included computer-aided instruction, 4 utilized human-patient simulation, 1 used both computeraided instruction and human-patient simulation, and 7 utilized virtual patients. Educational technology was employed with more than 2700 students at 12 colleges and schools of pharmacy in courses inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 23 publications
0
42
0
4
Order By: Relevance
“…7 We are the first to use the Qualtrics survey software as a framework for VPAs. 5 The use of Qualtrics, with branched-outcome logic and data collection capabilities, allowed for more complex scenarios and facilitated active student learning in higher levels of the Bloom's taxonomy cognitive learning domain. 4 However, the user interface did not aesthetically mimic an electronic health record and in the future we would like to make the scenarios more graphically appealing, real-life, and easier to use.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…7 We are the first to use the Qualtrics survey software as a framework for VPAs. 5 The use of Qualtrics, with branched-outcome logic and data collection capabilities, allowed for more complex scenarios and facilitated active student learning in higher levels of the Bloom's taxonomy cognitive learning domain. 4 However, the user interface did not aesthetically mimic an electronic health record and in the future we would like to make the scenarios more graphically appealing, real-life, and easier to use.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of technology in pharmacy education found that while computer-aided instruction revealed conflicting impact on learning, mannequin-based patients and virtual patient simulations had significant effects on learning. 5 Analyses of virtual patient use in pharmacy schools have usually compared before and after knowledge assessments while comparisons to paper-based scenarios or other teaching methods have also not been done or did not show significant differences. [9][10][11][12] The majority of virtual patient publications in the pharmacy and other healthcare fields have involved adult patient scenarios, [5][6][7] but pediatric patients have unique medication-related needs that would impact the creation and implementation of virtual patients for pharmacy education.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations